Migrating faith : Pentecostalism in the United States and Mexico in the twentieth century - Ramirez, Daniel, 1958- (University of North Carolina Press, 2015)
Daniel Ramírez's history of 20th century Pentecostalism in the US-Mexico borderlands argues that, because of the distance separating the transnational migratory circuits from domineering arbiters of religious and aesthetic orthodoxy in both the US and Mexico, the region was fertile ground for the religious innovation by which working-class Pentecostals expanded and changed traditional options for practicing the faith.